Implementation of Augmented Reality in Mathematics Learning on Mathematical Spatial Ability - Lubna Rihadatul 'Aisy; Adi Nur Cahyono; Zaenuri; Walid (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
Mathematics learning requires the support of effective instructional media and technology to enhance students’ mathematical spatial abilities. Augmented Reality (AR) has emerged as a promising technology for facilitating spatial learning, particularly in geometry-related topics. This systematic literature review aims to analyze research trends and the implementation of AR in mathematics learning with respect to mathematical spatial abilities, providing insights for future research and instructional design. The review employed the Systematic Literature Review (SLR) method, initially identifying 900 studies, of which 9 articles published between 2020 and 2025 met the inclusion and exclusion criteria. The findings reveal four major clusters of interconnected research themes, with mathematical spatial ability showing strong associations with spatial visualization, mental rotation, and spatial orientation. The analysis indicates an increasing research trend in recent years, highlighting AR’s role not only as a visualization medium but also as an effective pedagogical tool that supports the development of mathematical spatial abilities through interactive three-dimensional representations. These results suggest that AR-based learning has significant potential to enhance spatial understanding in mathematics education.